2018
DOI: 10.1038/s41598-018-34627-w
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Clinical Trial for Postoperative Complications after Ex-PRESS Implantation versus Trabeculectomy with 2-Year Follow-Up

Abstract: We compared complications between Ex-PRESS implantation and trabeculectomy for 2 years after surgery. Sixty-four open-angle glaucoma eyes were randomly assigned to treatment with trabeculectomy (n = 32) or Ex-PRESS implantation (n = 32). The primary outcomes were postoperative complications, including reduction of the endothelial cell density (ECD) of the cornea, cataract progression and the frequency of other late postoperative complications. The Ex-PRESS group had significantly greater reduction of postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 46 publications
5
47
0
2
Order By: Relevance
“…The physiopathological mechanism underlying the damage to the corneal endothelial cells following EX-PRESS implantation remains unknown, with recent data suggesting that it might be different from that of corneal endothelial cell loss after trabeculectomy. The corneal superior area, where the EX-PRESS device was inserted, was found to have significantly more severe corneal endothelial cellular density reduction than the inferior area 2 years after surgery, whereas no area dependency was observed in patients who underwent trabeculectomy [40].…”
Section: Corneal Decompensationmentioning
confidence: 86%
See 1 more Smart Citation
“…The physiopathological mechanism underlying the damage to the corneal endothelial cells following EX-PRESS implantation remains unknown, with recent data suggesting that it might be different from that of corneal endothelial cell loss after trabeculectomy. The corneal superior area, where the EX-PRESS device was inserted, was found to have significantly more severe corneal endothelial cellular density reduction than the inferior area 2 years after surgery, whereas no area dependency was observed in patients who underwent trabeculectomy [40].…”
Section: Corneal Decompensationmentioning
confidence: 86%
“…Recent studies evaluating longer follow-ups demonstrate a statistically significant reduction of the corneal endothelium cell density, which was found by Ishida et al 24 months after EX-PRESS implantation [38], compared to the normal corneal endothelium decrease rate of 0.6% per year [39]. While comparing postoperative complications between trabeculectomy and EX-PRESS implantation with 2 years of follow-up, Arimura et al showed that EX-PRESS is associated with a significantly greater reduction of corneal endothelial cell density than trabeculectomy, especially in the corneal area around the tube [40].…”
Section: Corneal Decompensationmentioning
confidence: 98%
“…The efficacy and safety of the Ex-PRESS shunt are already known, and the low complication rate compared to standard trabeculectomy as well as good IOP control has already been demonstrated. However, the follow-up of the previous reports is up to 3 years [24][25][26]40]. Moreover, all patients received anti-mitotic medication as adjuvant therapy for postoperative IOP control [24][25][26]40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the follow-up of the previous reports is up to 3 years [24][25][26]40]. Moreover, all patients received anti-mitotic medication as adjuvant therapy for postoperative IOP control [24][25][26]40]. The added value of our study is represented by a longer follow-up of patients with Ex-PRESS intervention without anti-mitotic medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation